2013
DOI: 10.1515/znc-2013-7-810
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Biochemical Stress Response to Chlorpyrifos in Tissues of the Edible Crab Barytelphusa guerini: Withdrawal of Exposure Improves the Nutritional Value

Abstract: The sublethal stress of the organophosphate insecticide chlorpyrifos was investigated in different tissues of the freshwater crab (Barytelphusa guerini). Crabs were exposed to 1/3 of LC50 concentrations for 7, 14, 21, and 28 days. After 28 days, they were released into fresh water and kept for 18 days for recovery. The study was conducted by estimating total proteins, amino acids, ammonia, urea, and glutamine levels, and protease, transaminases, and phosphatases activities. Total proteins level was decreased w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Furthermore, the 48 h LC 50 value of 19 mg l -1 and 96 h LC 50 value of 1.46 mg l -1 have been reported with juveniles of L. vannamei following exposure to 2 OP pesticides, fenitrothion (Lignot et al 1998) and methamidophos (García-de la Parra et al 2006), respectively. On the basis of the observation made in the present study (96 h LC 50 , 1.44 µg l -1 ) and previously reported results (Galindo-Reyes et al 1996, Ali et al 2009, Kumar et al 2010, Narra et al 2013, Samajdar & Mandal 2015, it may be concluded that L. vannamei juveniles are highly sensitive to CPF pesticide toxicity.…”
Section: Acute Toxicitysupporting
confidence: 83%
See 2 more Smart Citations
“…Furthermore, the 48 h LC 50 value of 19 mg l -1 and 96 h LC 50 value of 1.46 mg l -1 have been reported with juveniles of L. vannamei following exposure to 2 OP pesticides, fenitrothion (Lignot et al 1998) and methamidophos (García-de la Parra et al 2006), respectively. On the basis of the observation made in the present study (96 h LC 50 , 1.44 µg l -1 ) and previously reported results (Galindo-Reyes et al 1996, Ali et al 2009, Kumar et al 2010, Narra et al 2013, Samajdar & Mandal 2015, it may be concluded that L. vannamei juveniles are highly sensitive to CPF pesticide toxicity.…”
Section: Acute Toxicitysupporting
confidence: 83%
“…A significantly marked decrement in protein content (28−42%) in juveniles of L. vannamei on exposure to 4 organochlorine pesticides has been reported by Galindo-Reyes et al (1996). A progressive depletion in total protein content in gills, muscles, hepatopancreas and brain on exposure (28 DoE) to SL concentrations of CPF has been documented by Narra et al (2013). Furthermore, significant alterations in major biochemical constituents in the penaeid shrimp Metapenaeus monoceros on exposure to SL doses of endosulfan pesticide has also been reported (Suryavanshi et al 2009).…”
Section: Genotoxicity Evaluation In Gill Muscle and Haemolymph Cellsmentioning
confidence: 85%
See 1 more Smart Citation